Industrial Process Management Model to Improve Productivity and Reduce Waste - Oddershede-Herrera, A; Quezada-Llanca, L; Ortiz-Mendez, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
One of the challenges facing operations management is the design, choice, and implementation of action plans adapted to the magnitude of the deviations from the variables of an industrial process. Making conscious and quick decisions is crucial to achieving improvements in productivity. This will be achieved if the organization s internal and external communication model is strategically designed, considering specific cultural factors and the symmetry or asymmetry required in the communication model. However, how do we organize ourselves and through what channels do we communicate within a production process to generate Big Data that combines data from technologies and the perception, comprehension, and projection of experienced humans? Our hypothesis suggests that the implementation of our model generates a continuous improvement system that could provide significant benefits to the company by connecting management with the place where the work happens (Gemba), streamlining multiple processes, thereby fostering sustainability. The developed model, "Group Situational Awareness Model", was implemented in an operations management team, following the guidelines of an action researcher methodology. This resulted in the design of an operations management model and a detailed methodology for its implementation, achieving significant improvements in the metrics of the current process, making it a success story.